Characterisation of serum progesterone and progesterone-induced blocking factor (PIBF) levels across trimesters in healthy pregnant women - Lim, Mark Kit (2021)
Progesterone-induced blocking factor (PIBF), which plays an important role in maintaining healthy pregnancies, has shown great promise as a prognostic biomarker for threatened miscarriage. To better characterise the physiological trends of progesterone and PIBF, we analysed serum progesterone and PIBF concentrations in healthy non-pregnant and pregnant women across trimesters. We saw increasing concentrations of progesterone and PIBF in pregnant women with advancing trimesters. The serum progesterone and PIBF percentiles across gestational age in healthy pregnancies can be used as a guide for the formulation of reference ranges. We also demonstrated a significant positive correlation between progesterone and PIBF levels. This study demonstrates increasing progesterone and PIBF concentrations in later trimesters and underscores the importance of progesterone and PIBF in healthy pregnancies. Characterisation of progesterone and PIBF across gestational age in healthy pregnant women may help to prognosticate pregnancy viability and support further research into the importance of progesterone and PIBF in the maintenance of healthy pregnancies.